2009
DOI: 10.1124/mol.109.061887
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rad51 Down-Regulation and Extracellular Signal-Regulated Kinases 1 and 2 Inactivation in Emodin and Mitomycin C-Induced Synergistic Cytotoxicity in Human Non–Small-Cell Lung Cancer Cells

Abstract: Emodin (1,3,8-trihydroxy-6-methyl-anthraquinone) is a natural anthraquinone derivative found in the roots and rhizomes of numerous plants. It is a tyrosine kinase inhibitor and has anticancer effects on lung cancer. Rad51 plays a central role in homologous recombination, and high levels of Rad51 expression are observed in chemo-or radioresistant carcinomas. Our previous studies have shown that the mitogen-activated protein kinase kinase (MKK) 1/2-extracellular signal-regulated kinase (ERK) 1/2 signal pathway m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…It has been seen that the expression of both these proteins are high in cancer, causing instability of the genome. Treatment of emodin increases the antitumor antibiotic, mitomycin C (MMC)-induced cytotoxicity via ERK1/2 inactivation and Rad51 down-regulation in lung cancer H1703 or A549 cells [53] and has an additive effect on cisplatin-induced cytotoxicity via downregulating ERCC1 expression in human NSCLC cells through regulation of the ERK1/2 signaling pathway [54]. In human nonsmall cell lung cancer (NSCLC), emodin with (or without) capecitabine induced cytotoxicity by down-regulating the expression of Rad51 and ERCC1 [47,55].…”
Section: Anti-proliferative Effects Of Emodinmentioning
confidence: 99%
“…It has been seen that the expression of both these proteins are high in cancer, causing instability of the genome. Treatment of emodin increases the antitumor antibiotic, mitomycin C (MMC)-induced cytotoxicity via ERK1/2 inactivation and Rad51 down-regulation in lung cancer H1703 or A549 cells [53] and has an additive effect on cisplatin-induced cytotoxicity via downregulating ERCC1 expression in human NSCLC cells through regulation of the ERK1/2 signaling pathway [54]. In human nonsmall cell lung cancer (NSCLC), emodin with (or without) capecitabine induced cytotoxicity by down-regulating the expression of Rad51 and ERCC1 [47,55].…”
Section: Anti-proliferative Effects Of Emodinmentioning
confidence: 99%
“…Recently, Lin, Y W et al have reported a variety of drugs that inhibit the expression of Rad51, such as DIDS [16], erlotinib [17], emodin [18], and gefitinib [19]. Therefore, these drugs can be investigated in future studies, particularly to test if their combination can enhance the therapeutic effect against osteosarcoma.…”
Section: Discussionmentioning
confidence: 94%
“…Aloe emodin also induced apoptosis in lung non-small carcinoma cells, H460, through inactivation of the ERK signalling pathway (27). Elevated levels of Rad51 expression seen in chemo or radioresistant lung carcinomas are decreased in nonsmall-cell lung cancer cells, H1703 and A549 by the synergistic effect of emodin (Rheum palmatum L root and rhizome extracts) with anti-tumor antibiotic mitomycin C through inactivation of ERK pathway (28). It enhanced the cytotoxicity effect of cisplatin in advanced non-small cell lung cancer cells, (NSCLC) through the downregulation of excision repair cross-complementation 1 (ERCC1), an enzyme crucial for the removal of adducts from genomic DNA, and inactivation of ERK survival pathway (29).…”
Section: Discussionmentioning
confidence: 99%